Health Education Using Learning Videos On The Level Of Teeth Brushing Skills In School-Age Children At Technical Implementation Unit Of Ngrendeng 01 Public Elementary School - Putri Dwi Wulandari; Muhammad Ali Sodik (Universitas STRADA Indonesia, 2022)
Dental and oral health could be achieved with correct and excellent dental and oral hygiene maintenance. School-age children still do not know about the maintenance of dental and oral hygiene, it is proven that the caries rate that occurs at the age of 10-14 years is 73.4% and the behavior of brushing teeth carried out at the right time is only 2.1%. Health education methods with learning video media can teach children and improve children's skills in brushing teeth. The purpose of this study was toanalyze the effect of health education using learning videos on the level of teeth brushing skills in school-age children at technical implementation unit of ngrendeng 01 public elementary school. This type of research is Pre Experiment used a one group pretest posttest design with a sample of 36 respondents selected using probability stratified random technique sampling. The research instrument used was an observation sheet. The data analysis technique used the Wilcoxon Signed Rank Test. The results of the Wilcoxon sihowed tha rank test statistic obtained p-value = 0.000, so that the p-value < (0.05). This reserearch can be concluded that there is an effect of health education using learning videos on the level of tooth brushing skills in early hildhood students at technical implementation unit of ngrendeng 01 public elementary school.